Mungkahing pinalatuntunang talasalitaan batay sa ilang hudyat para sa baitang VI sa kaligirang pang-unang wika - Cosio, Rosalinda (Gomez) 1928- ([s.n.], 1972)
Programmed instruction was used in teaching pupils on how to form, develop, and enrich his vocabulary. A programmed text for teaching vocabulary words based on some clues was prepared. The lesson was presented in frames that use the linear method. The program is composed of three parts, namely, word meaning based on morphological clues, morphophonemic clues and contextual clues.